Comparison of mechanical performance between friction-stir spot welded and adhesive bonded joints (Fracture and Structural Integrity, 2020)
The main objective of this study is to compare the mechanical strength of friction stir spot welded (FSSW) joints and adhesive bonded single lap ones. The present study aims to compare the morphology and strength of welded and adhesive bonded joints. The welded joints were done by friction stir spot welding and the adhesive bonded ones by the use of the adhesive Araldite 420 A/B. The produced joints were subjected to morphology and microstructure analyzes, microhardness tests, tensile-shear tests and local strain analyzes. The welded joints have higher strength than adhesive-bonded joints. However, this difference is insignificant, around 5%, which is covered by the standard deviation. The connection by FSSW proves to be an alternative to adhesive bonded joints, offering the same strength, but with the connection at isolated points, inducing local stress concentration.
Keywords: Adhesive bonding; Friction-stir welding; Aluminium adherends